Konsep Alam Menurut Daud Al-Fatani dalam Karyanya Manhal Al-Ṣāfī: Analisis dari Perspektif Astronomi Islam: The Concept of Universe According to Daud al-Fatani in His Work Manhal Al-Ṣāfī: An Analysis from Islamic Astronomy Perspective - Abdul Niri, Mohammaddin; Sa’ari, Che Zarrina; Man, Sa’adan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The discourse on the concept of universe offered by traditional scholar is valuable intellectual treasures for Muslims in the Malay world. Daud al-Fatani was amongst the traditional scholar that has contributed his thoughts on the discourse of the concept and it is presented in his sufism literature namely Manhal al-Safi. In the current context, the crucial question has to be studied is how to scrutinize and conclude the concept through an integrated framework of thinking that not only taking into account the Islamic fundamental knowledge which consists of theology, jurisprudence and sufism, but also utilize current scientific knowledge. To that end, we propose the framework of Islamic astronomy and this article discusses how the framework formulates the concept of universe according to Daud al-Fatani from his work Manhal al-Ṣāfī. Finally, the study found that Daud al-Fatani’s concept of universe in his work is formed from the mushāhadah that derived from the determination of heart in allowing the word of faith lā ilāha illā Allāh.